Toward knowledge-based liver surgery: holistic information processing for surgical decision support - März, Keno; Hafezi, Mohammadreza; Weller, T.; Saffari, Afshin; Nolden, M.; Fard, N.; Majlesara, Ali; Zelzer, S.; Maleshkova, M.; Volovyk, M.; Soleymanzadeh Gharabaghi, Negin; Wagner, Martin; et al. (International journal of computer assisted radiology and surgery, 2015)
Malignant neoplasms of the liver are among the most frequent cancers worldwide. Given the diversity of options for liver cancer therapy, the choice of treatment depends on various parameters including patient condition, tumor size and location, liver function, and previous interventions. To address this issue, we present the first approach to treatment strategy planning based on holistic processing of patient-individual data, practical knowledge (i.e., case knowledge), and factual knowledge (e.g., clinical guidelines and studies).
Gesehen am 08.06.2020